COVID-19 recovery: benefits of multidisciplinary respiratory rehabilitation - Wim Janssens; Greet Hermans; Rik Gosselink; Daniel Langer; Thierry Troosters; Hilde Beyens; Stephanie Everaerts; Arne Heyns; Natalie Lorent (BMJ Open Respiratory Research)
Many patients struggle with ongoing symptoms in different domains (physical, mental, cognitive) after hospitalisation for COVID-19, calling out for a multidisciplinary approach. An outpatient multidisciplinary rehabilitation programme, according to a respiratory rehabilitation strategy, was set up for adult patients who were able to attend group sessions during 12 weeks. Results of 22 adult patients with COVID-19, of which 15 had required intensive care, were analysed and some general impressions and challenges of rehabilitation in COVID-19 were reported. Impressive results on physical recovery were determined after 6 weeks and 3 months, with significant improvement of lung function, muscle force and exercise capacity variables. A positive evolution of mental and cognitive burden was present, although less pronounced than the physical recovery. These mental and cognitive consequences seem, next to musculoskeletal and medical complications, the most challenging aspect of rehabilitating patients with COVID-19. These real-world data show feasibility and efficiency of a multidisciplinary respiratory rehabilitation programme after moderate to severe COVID-19 disease.